Development of Mobile Learning in Faculty of Economics, Bina Nusantara University - Herru Darmadi; Suryadiputra Liawatimena (Bina Nusantara University, 2017)
The research wanted to find the workflow and solution by developing m-learning object for Android and iOS-based smartphone and tablet that supported interactive multimedia. The research began with analysis, design, implementation, and evaluation. Currently, the learning objects were not compatible with mobile devices. To overcome this problem, the research focused on designing the instructional design for m-learning and the development of interactive multimedia. Instructional design was created by the collaboration of the subject matter expert and instructional designer. M-learning was designed using UML and developed using Adobe AIR technology. The implementation of this research was a prototype of m-learning for concept of cost in Faculty of Economics, Bina Nusantara University. Then, the evaluation was conducted by distributing m-learning object to 32 selected students by simple random sampling in their first week of lectures in February 2014. The observation was conducted during m-learning object installation and initial learning process. At the end of the second week of the experiment, summative assessment and questionnaire were given to students. The results show that m-learning object is compatible with mobile devices. The students also say that m-learning is easy to use and helpful for their learning.